Surface Evaluation of Tricalcium Phosphate Bioceramic Coating on SS-316L by Electrophoretic Deposition - Hermana, Gita Novian; Nugraha, Dhion Khairul; Nadi, Muhammad Rizki Gorbyandi; Sektiono, Moch. Wisnu Arif; Mayello, Randy Mediawan; Farhan, Miftah; Kusuma, Nirmala Cahya; Alfayed, Naufal Alden; Rizqi, Fauzi Muhamad (Universitas Negeri Semarang, 2024)
The development of orthopedic implant materials has become an important topic of discussion lately. The SS-316L alloy is widely used as an implant material due to its relatively low cost, corrosion resistance, and ease of production. However, metal alloys, especially SS-316L, are prone to ion release into the blood over time. Therefore, TCP or tricalcium phosphate [Ca3(PO4)2] is needed to coat the surface of SS-316L, preventing ion release into the blood and enhancing the biocompatibility of the implant material. In this study, TCP coating was applied to the SS-316L substrate using the electrophoretic deposition technique. The influence of deposition time on changes in microstructure and mechanical properties is the main focus of this study. The results of the coating technique indicate that the deposition yield increases with the deposition time. Morphological testing results show that increasing deposition time improves coating quality by increasing the thickness of the coating layer and preventing layer peeling. The coating process also reveals the accumulation of layers in certain areas and the formation of thin layers in other regions. A deposition time of 30 minutes results in a coating thickness ranging from 48.7 to 57.9 µm. Hardness testing, conducted with indentation loads of 50, 100, and 300 gf, indicates that longer deposition times and higher indentation loads during hardness testing result in reduced material hardness.